Operational Improvements In It-Based E-Commerce Companies Using Monday.Com - Ng Poi Wong; Darwin Darwin; Riche Suwandy (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
E-commerce innovations must continue to be created so that customers can experience the same feelings when shopping online as they do in real stores. Collaboration and communication between teams are required in order for Monday.com tools to be used in its operations as a means of improving the operational system. The methodology utilized in this study was to read the literature and then process the data received from the results of the literature. The findings of data processing suggest that Monday.com's tools are now popular, indicating that Monday.com's potential to improve operations in e-commerce enterprises may be demonstrated by the availability of numerous visual boards. This graphic also includes a complete filtering feature, as well as an API that greatly facilitates the integration process with e-commerce platforms.